Assessment of the greenery planting level in sanitary protection zones of the Dnipropetrovsk industrial enterprises (Environment & Health, 2016)
Objective. We studied a level of the greenery planting in the sanitary protection zones (SPZ) of the Dnepropetrovsk industrial enterprises.Materials and мethods. We applied the Normalized Difference Vegetation Index (NDVI) for the assessment of the level of territories’ greening planting and the quality of green space. For its calculation we used the multispectral aerial photographs obtained from the archives of satellite imagery Landsat 8. Processing of aerial photos, calculation of average-seasonal values of the NDVI, as well as their classification with a further zone-statistical analysis at the territories of the SPZ were performed in the program ESRI ARCMAP 9.Results. The green areas at the territories of the SPZ were determined to be placed irregularly. A significant part of the SPZ territories of the industrial enterprises is characterized by rare vegetation and open soil. The enterprises that didn’t meet the requirements for the amount of vegetated areas of the SPZ were revealed as a result of zone-statistical analysis.
Keywords: sanitary protection zone; greenery planting of the territory; vegetation in-dices; industrial enterprises; remote sensing